Development of a new dipstick (Cholkit) for rapid detection of Vibrio cholerae O1 in acute watery diarrheal stools. - Md Abu Sayeed; Kamrul Islam; Motaher Hossain; Noor Jahan Akter; Md Nur Alam; Nishat Sultana; Farhana Khanam; Meagan Kelly; Richelle C Charles; Pavol Kováč; Peng Xu; Jason R Andrews; et al. (Public Library of Science (PLoS), 2018)
Recognizing cholera cases early, especially in the initial phase of an outbreak and in areas where cholera has not previously circulated, is a high public health priority. Laboratory capacity in such settings is often limited. To address this, we have developed a rapid diagnostic test (RDT) termed Cholkit that is based on an immunochromatographic lateral flow assay for the diagnosis of cholera cases using stool. Cholkit contains a monoclonal antibody (ICL-33) to the O-specific polysaccharide (OSP) component of V. cholerae O1 lipopolysaccharide, and recognizes both Inaba and Ogawa serotypes. We tested the Cholkit dipstick using fresh stool specimens of 76 adults and children presenting with acute watery diarrhea at the icddr,b hospital in Dhaka, Bangladesh. We compared Cholkit's performance with those of microbial culture, PCR (targeting the rfb and ctxA genes of V. cholerae) and the commercially available RDT, Crystal VC (Span Diagnostics; Surat, India). We found that all stool specimens with a positive culture for V. cholerae O1 (n = 19) were positive by Cholkit as well as Crystal VC. We then used Bayesian latent class modeling to estimate the sensitivity and specificity of each diagnostic assay. The sensitivity of Cholkit, microbiological culture, PCR and Crystal VC was 98% (95% CI: 88-100), 71% (95% CI: 59-81), 74% (95% CI: 59-86) and 98% (95% CI: 88-100), respectively. The specificity for V. cholerae O1 was 97% (95% CI: 89-100), 100%, 97% (95% CI: 93-99) and 98% (95% CI: 92-100), respectively. Of note, two Crystal VC dipsticks were positive for V. cholerae O139 but negative by culture and PCR in this area without known circulating epidemic V. cholerae O139. In conclusion, the Cholkit dipstick is simple to use, requires no dedicated laboratory capacity, and has a sensitivity and specificity for V. cholerae O1 of 98% and 97%, respectively. Cholkit warrants further evaluation in other settings.